Fish nuggets, Adequacy of protein, Nutritional Status, Cognitive - Nonce Nova Legi (Jurnal GIZIDO, 2012)
physical and mental development. Normal nutritional level state is reached whenthe optimal nutritiona needs are met. Intellectual ability of children to determinethe success of children in gaiwing achievement. Purpose of this research is toknow the relationship of nutritional status and academic achievement of children.The design of this research is deskriptif cross sectional. Sample was collectedwith a total sampling, where the amount of sample are 212 student. Datacollection technique is direct observation. Analisis using chi square test, at 95%(α 0,05) confidence level the value of p = 0,00 < 0,05. Ha showed acceptableresult. Conclusion : There was significant correlation with the nutritional satus ofstudent learning achievement.